Edukasi Perencanaan Keuangan dan Pengelolaan Utang untuk Komunitas Perempuan Rentan - Amalia, Via; Ekaviana, Dessy; Eriyani, Eriyani; Fatimah, Siti (Institut Agama Islam Negeri Kerinci, 2025)
This community service aimed to enhance financial literacy by focusing on financial planning and debt management for vulnerable women in Sumurejo Village, Gunungpati District, Semarang City. The activity was conducted on August 13, 2025, through interactive lectures, group discussions, and case-based practices with 30 women participants identified as having limited financial access and being vulnerable to debt traps. The program emphasized practical strategies in budgeting, savings, and responsible debt use. Evaluation using pre-test and post-test revealed a significant improvement: participants’ ability to prepare a simple household budget increased from 30% to 85%, and their understanding of the difference between productive and consumptive debt rose from 25% to 85%. These results indicate that the training not only increased financial awareness but also provided practical skills applicable in daily life. This activity is expected to contribute to women’s economic empowerment and strengthen sustainable household financial resilience.